2008
DOI: 10.1158/1940-6207.prev-08-b139
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B139: Effect of wheat grass juice in supportive care of terminally ill solid organ cancer patients: Experience from eastern India

Abstract: B139 Background The solid content of juice made from wheat grass is 70% chlorophyll. Chlorophyll is often referred to as “The blood of plant life” and has almost the same chemical structure as hemoglobin. Chlorophyll cleanses the blood by improving the supply of oxygen to the circulatory system. Wheat grass is also a complete protein with about 30 enzymes, vitamins and minerals. Wheat grass juice has been proven over many years to benefit people in numerous w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A rapid 3-5-fold increase has been observed which is "significantly greater than any of the pharmaceutical inducers available‖. The use of wheatgrass extract may eventually result in an improved quality of life for thalassemics [37]. A pilot study showed that when 100 ml of wheatgrass juice, extracted daily from a 5-6‖ tall plant, fed to human beings for up to 6 months, was given to 38 thalassemic children, and had beneficial effect on transfusion requirements in 50% patients of Bthalassemia major.…”
Section: Wheatgrass -A Boon For Thalassemia Patientsmentioning
confidence: 99%
“…A rapid 3-5-fold increase has been observed which is "significantly greater than any of the pharmaceutical inducers available‖. The use of wheatgrass extract may eventually result in an improved quality of life for thalassemics [37]. A pilot study showed that when 100 ml of wheatgrass juice, extracted daily from a 5-6‖ tall plant, fed to human beings for up to 6 months, was given to 38 thalassemic children, and had beneficial effect on transfusion requirements in 50% patients of Bthalassemia major.…”
Section: Wheatgrass -A Boon For Thalassemia Patientsmentioning
confidence: 99%